Binding of translationally controlled tumour protein to the N-terminal domain of HDM2 is inhibited by Nutlin-3 - Funston, Garth. (2013)
Translationally Controlled Tumour Protein (TCTP), a highly conserved protein present in all eukaryotic organisms, has a number of intracellular and extracellular functions including an anti-apoptotic role. TCTP was recently shown to interact with both p53 and HDM2, inhibiting auto-ubiquitination of the latter and thereby promoting p53 degradation. In this study, we further investigated the interaction between TCTP and HDM2, mapping the reciprocal binding sites of TCTP and HDM2. TCTP primarily interacts with the N-terminal, p53-binding region of HDM2 through its highly basic domain 2. Furthermore, we discovered that Nutlin-3, a small molecule known to promote apoptosis and cell cycle arrest by blocking binding between HDM2 and p53, has a similar inhibitory effect on the interaction of HDM2 and TCTP. This result may provide an additional explanation of how Nutlin-derived compounds currently in clinical trials function to promote apoptosis in cancer cells.